A Comparison of the Morbidities Associated with Different Early Treatments in Tubo-Ovarian Abscess Patients - Sumanta Saha; Sujata Saha (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: A tubo-ovarian abscess needs hospitalization and early treatment with parenteral antibiotics only or along with imaging-guided drainage. This meta-analysis juxtaposes between these interventions - the length of stay in hospital in days, surgery requirement for those not responding to the initial treatment, and readmission.